2021
DOI: 10.1186/s12947-020-00231-0
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial functional assessment and mortality in patients with severe aortic stenosis with sinus rhythm

Abstract: Background Aortic valve stenosis (AS) is the most common primary valvular heart disease leading to surgical or percutaneous aortic valve replacement (AVR) in Europe and its prevalence keeps growing. While other risk factors in severe AS are well documented, little is known about the prognostic value of left atrial (LA) function in AS. Our aim is to clarify the relationship between LA function measured at severe AS diagnosis (evaluated by means of volumetric assessment) and all-cause mortality d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Moreover, LA longitudinal strain parameters were inversely correlated with the worsening of NYHA class. These findings are consistent with the greater ability of LA mechanics in predicting prognosis when compared with LV mechanics analysis ( 34 , 152 , 153 ). Galli et al ( 35 ) demonstrated that LA reservoir function (<21%) is predictive of major adverse cardiac events and HF in 128 symptomatic and asymptomatic patients with severe AS, while LV function parameters (ejection fraction and global longitudinal strain) are not.…”
Section: La Mechanics In Hf Stagessupporting
confidence: 82%
“…Moreover, LA longitudinal strain parameters were inversely correlated with the worsening of NYHA class. These findings are consistent with the greater ability of LA mechanics in predicting prognosis when compared with LV mechanics analysis ( 34 , 152 , 153 ). Galli et al ( 35 ) demonstrated that LA reservoir function (<21%) is predictive of major adverse cardiac events and HF in 128 symptomatic and asymptomatic patients with severe AS, while LV function parameters (ejection fraction and global longitudinal strain) are not.…”
Section: La Mechanics In Hf Stagessupporting
confidence: 82%
“…Both of them were also notably associated with AS severity [34]. Additionally, Ferreira et al have shown that defective LA emptying fraction was a strong predictor for all-cause mortality [35].As for LA strain, studies have shown that LA strain was related to LV dysfunction and AS severity, being also an independent predictor for HF hospitalization, all-cause mortality, and new-onset atrial brillation, regardless of LA dilation [36,37]. Recently, Kim et al have conducted a CMR study in which they have suggested that LA peak longitudinal strain might predict cardiovascular events in AS [38], but several studies have shown that traditional CMR methods might have questionable reliability, requiring further adjustments [39].…”
Section: Discussionmentioning
confidence: 96%
“…LA geometry and function are well-described prognostic discriminators for multiple left heart conditions. For patients with aortic stenosis, both LA size and function have demonstrated independent incremental prognostic information 32 , 33 ; however, current studies quantifying LA function using strain imaging are limited in both number and sample size. Moreover, the independent prognostic value of LA functional recovery following TAVR and whether intervention at an earlier stage may afford biologically plausible protection from the known consequence of adverse LA remodelling, such as new onset AF, are yet to be demonstrated in large prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%